Mechanism and Synthesis of Yttrium Iron (Y-Fe) Alloy by Low Temperature Process Using Calcium as Reductant - Marimuthu Ilayaraja; L. John Berchmans; Sankara Raman Sankaranarayan (Archives of Metallurgy and Materials, 2019)
In this paper, study the preparation of Y-Fe alloy by reduction-diffusion process, which is novel technique for producing an alloy from its ores directly at different temperatures. From this work, investigates the particles size and morphology structure of alloy by X-Ray Diffraction (XRD), Energy dispersive-X-ray analyzer (EDAX) and Scanning Electron Microscope (SEM) respectively. Here study the thermodynamics of property of system such as Gibbs free energy and reaction kinetics of system respectively. The Vibrating Sample magnetometer (VSM) is used to study the magnetic properties of alloy such as cocerviety, saturation magnetization and retentivity.